Caracterização e estudo das propriedades ópticas de íons de Neodímio em uma matriz vítrea à base de óxidos - Serqueira, Elias Oliveira (2005)
The material host, considered in this research, for ions of Neodymium was glass matrix SNPZ (40SiO2 . 30Na2CO3 . 20PbO . 10ZnO (%mol)) doped with XNd2O3 (%wt), where X = 0.1; 0.3; 0.5; 0.7; 0.9; 1.1; 1.3; 1.5; 1.7; 1.9. The specters of optic absorption of doped matrix glass SNPZ with ions Nd3+ had presented bands of optic absorption (OA) centered around 431, 474, 514, 530, 586, 630, 685, 739, 804, 876 and 1598 nm, gotten ambient temperature. Already the photoluminescence specters (PL) had presented bands centered around 811, 880, 1060, 1330 nm, gotten, also, to the ambient temperature, using the line of excitement of 514.5 nm (19436 cm-1) of an argon laser, for pump of electrons of the 4I9/2 state for 4G9/2 + 4G7/2 + 2K13/2 of ions of Neodymium inserted in glass matrix SNPZ, where 4F3/2 occurred a nonradiative decline until the state. The difference of energy of the intermediate states between 4G9/2 + 4G7/2 + 2K13/2 and 4F3/2 is of the order of the corresponding energy to the ways of vibration of glass matrix SNPZ, that are of 421, 515 and 851 cm-1 in agreement the Raman specters, gotten to the ambient temperature. To get the spectroscopic parameters one used the calculations of the Theory of Judd-Ofelt, where presented a maximum quantum efficiency of 97.8 % glass doped in matrix SNPZ with 0.7 Nd2O3 (%wt), correspondent the 9.490 x 1019 ions/cm3 and verified an experimental lifetime of 302 µs for the state 4F3/2. Ahead of this, it can be concluded that glass matrix SNPZ makes possible to be an ideal host for ions of Neodymium in relation to the excessively material ones. In this work of research it was verified that the length of migration of the photon is maximum for doped glass matrix SNPZ with 1.1 Nd2O3 (%wt), correspondent 1.22 x 1020 ions/cm3. At last, for the fact of the ion of Nd3+ to present emission and absorption around 880 nm can be used doped glass matrix SNPZ with ions of Nd3+ as amplifying optic. Being able to conclude that it exists a distance it criticizes that it favors the diffusion of photons, a time that the concentration is related with distance between ions.